Difference of color stability of E-glass fiber dental and E-glass fiber non dental FRC: Perbedaan stabilitas warna FRC E-glass fiber dental dan E-glass fiber non dental - Sugeng Andi Purnama; Widya Puspita Sari; Resa Ferdina (Makassar Dental Journal, 2022)
The fiber that is most often used in dentistry is E-glass fiber, but in Indonesia E-glass fiber dental is limited by quantity and relatively expensive. E-glass fiber non dental was chosen as an alternative because the composition is almost the same as E-glass fiber dental and commonly used in the engineering world as a booster in the manufacture of gypsum panels, sculptures and automotive components. This study is aimed to determine the color stability difference between fiber reinforced composite (FRC) E-glass fiber dental and E-glass fiber non dental. This quantitative research is an experimental laboratory with a one group pretest and posttest research design. The sample is circular in shape with diameter 13 mm and height 2 mm consisted of E-glass fiber dental group and the E- glass fiber non dental group consisting of 4 samples for each group and given silane. After the color test using Spectrophotometer UV-Vis where the absorbance and wavelength values obtained will be calculated for the area so that the L*a*b* value and analysed using independent sample t-test, it was stated that there was no significant difference between the color of the fiber reinforced composite E-glass fiber dental and the E-glass fiber non dental. It is concluded that the use of E-glass fiber non dental can be used as a clinical standard because it has a good color stability value similar to that of E-glass fiber dental.